The relationship between tethered swimming, anaerobic critical velocity, dry-land strength, and swimming performance. (4th May 2022) - Ruiz-Navarro, Jesús J.; Gay, Ana; Cuenca-Fernández, Francisco; López-Belmonte, Óscar; Morales-Ortíz, Esther; López-Contreras, Gracia; Arellano, Raúl
ABSTRACT: This study aimed to 1) examine the associations between two swim-specific measures of anaerobic performance and dry-land strength-based variables; 2) study the association between the aforementioned variables with swimming performance and its kinematics; 3) analyse sex-induced differences. Twenty-three regional-national swimmers performed five countermovement-jumps and pull-ups, 50-m front crawl, two 30-s tethered-swimming tests at 0 and 1.124 m·s −1 water flow speed. Moreover, 10, 15, 20, and 25-m maximal front crawl were performed to determine anaerobic critical velocity (AnCV). The AnCV was positively correlated with tethered swimming variables in both conditions and dry-land-based variables in both sexes (p < 0.05). Tethered-swimming variables in both conditions were correlated with pull-ups' average propulsive force in males (p < 0.05). 50-m swimming performance was positively associated with AnCV, tethered-swimming variables, countermovement-jump height, and pull-ups' average propulsive force for both sexes (p < 0.05). Stroke rate (SR) was positively associated with AnCV in males and females (p < 0.05). Stroke length was correlated with tethered-swimming variables in males (p < 0.05). Except for SR, males presented higher values than females (p < 0.05). Depending on the conditions of their training environment, coaches might use the AnCV and tethered-swimming variables as interchangeable tools for evaluating anaerobic performance.